2023
DOI: 10.1002/vetr.3054
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of mammary tumours in bitches under veterinary care in the UK in 2016

Abstract: BackgroundThere is limited information on the epidemiology of canine mammary tumours. This study aimed to estimate the incidence and risk factors for mammary tumours in UK bitches.MethodsA nested case–control study was conducted within VetCompass to estimate the frequency and risk factors for clinically diagnosed mammary tumours during 2016 (VetCompass study). A second case–control study explored further breed associations for cases confirmed histopathologically compared to the VetCompass controls (laboratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In 2005–2013, analysis of CMTs in the Venice and Vicenza provinces showed a standardized incidence rate of 250/100,000 dogs/year. Recently, Varney et al (2023) reported the frequency of CMTs in bitches as 1340.7 per 100,000 dogs in 2016 in the UK [ 3 ]. A study by Zheng et al (2022) showed that the relative incidence of CMTs in Mainland China between 2017–2021 was 46.71%, with a similar number of malignant and benign forms [ 4 ].…”
Section: Canine Mammary Tumorsmentioning
confidence: 99%
“…In 2005–2013, analysis of CMTs in the Venice and Vicenza provinces showed a standardized incidence rate of 250/100,000 dogs/year. Recently, Varney et al (2023) reported the frequency of CMTs in bitches as 1340.7 per 100,000 dogs in 2016 in the UK [ 3 ]. A study by Zheng et al (2022) showed that the relative incidence of CMTs in Mainland China between 2017–2021 was 46.71%, with a similar number of malignant and benign forms [ 4 ].…”
Section: Canine Mammary Tumorsmentioning
confidence: 99%
“…The development of mammary tumours is complex and multifactorial. Age is one of the most relevant factors as the incidence of mam- (Donnay et al, 1994;Egenvall et al, 2005;Richards et al, 2001;Salas et al, 2015;Taylor et al, 1976;Varney et al, 2023;Zatloukal et al, 2005). Furthermore, breed (springer spaniel, cocker spaniel, boxer, poodle, dachshund; large breeds >small breeds), obesity at 1 year of age, hormone treatment and repeated pseudopregnancies (Dobson, 2013;Donnay et al, 1994;Egenvall et al, 2005;Gupta, 2012;Jitpean et al, 2012;Oliveira et al, 2022;Pastor et al, 2018;Pérez Alenza et al, 1998;Sonnenschein et al, 1991;Varney et al, 2023) and even alterations in gene expression by epigenetic mechanisms are reported predisposing factors (Borges, 2022).…”
Section: Mammary Tumoursmentioning
confidence: 99%
“…Age is one of the most relevant factors as the incidence of mam- (Donnay et al, 1994;Egenvall et al, 2005;Richards et al, 2001;Salas et al, 2015;Taylor et al, 1976;Varney et al, 2023;Zatloukal et al, 2005). Furthermore, breed (springer spaniel, cocker spaniel, boxer, poodle, dachshund; large breeds >small breeds), obesity at 1 year of age, hormone treatment and repeated pseudopregnancies (Dobson, 2013;Donnay et al, 1994;Egenvall et al, 2005;Gupta, 2012;Jitpean et al, 2012;Oliveira et al, 2022;Pastor et al, 2018;Pérez Alenza et al, 1998;Sonnenschein et al, 1991;Varney et al, 2023) and even alterations in gene expression by epigenetic mechanisms are reported predisposing factors (Borges, 2022). Intact female dogs were reported to have a threefold to fourfold or higher increased risk to develop a mammary tumour and more frequently have multiple tumours in comparison to gonadectomised dogs, whereas gonadectomy decreased the odds of developing mammary tumour as well as mortality rate due to mammary tumour about threefold (Beaudu-Lange et al, 2021;Gedon et al 2021b;Grüntzig et al, 2016;Misdorp, 1988;Priester, 1979;Schneider et al, 1969;Taylor et al, 1976;Varney et al, 2023).…”
Section: Mammary Tumoursmentioning
confidence: 99%
See 1 more Smart Citation